Using isotonic magnesium sulfate nebulization as an adjuvant treatment for moderate acute exacerbation of bronchial asthma (aeba) in adult comparing with salbutamol alone: a double blinded, randomised control trial - Ket Keong, Liew (2015)

(untitled)
Objective The aim of this study is to evaluate the efficacy of single dose nebulized magnesium sulfate in augmenting bronchodilatory effect of salbutamol in acute asthma as compare to salbutamol alone. In addition, we also observe for any significant reduction in total treatment duration in this two study groups. Methodology This was a double blinded, randomized controlled trial, conducted in Emergency Department of Hospital Universiti Sains Malaysia, Kelantan between 1st October 2013 and 1st October 2014. We enrolled a total of 120 patients with moderate acute exacerbation of bronchial asthma, all the patients were then randomized into two groups via block randomization technique. Group A (n=60) nebulized with salbutamol only (5mg), Group B (n=60) nebulized with isotonic magnesium sulfate (7.5% w/v) plus salbutamol (5mg). Blood pressure, pulse rate, respiratory rate, oxygen saturation and peak expiratory flow rate (PEFR) of each patient were measured at baseline and at 20 minutes post-treatment. Total duration of treatment started from time of enrollment until achievement of predicted PEFR > 80% was recorded. Results The 60 patients enrolled in each treatment arm had comparable baseline demographic and clinical characteristics. At 20 minutes post-treatment, Group A and Group B showed statistically significant improvement in PEFR (100±61 L/min and 87±42 L/min respectively, p value <0.001). Group B showed significant reduction of mean respiratory rate and improvement in mean oxygen saturation (p value <0.001). However, there were no statistically significant differences in means improvement of PEFR and reduction of total duration of treatment between two groups. We did not observe any adverse effect from treatment at all time. Conclusion In conclusion, the use of MgSO4 as an adjuvant to salbutamol nebulization in moderate AEBA patient does not show any superiority in their therapeutic effect in comparing to salbutamol alone. However, paired t-test done on group B population has shown the feasible bronchodilatory property of MgSO4, it is able to bring about a statistically significant decrease in respiratory rate and improvement in oxygen saturation. In future study, we suggest a pilot study to be conducted to establish the dose-response relationship of magnesium sulphate in the treatment of acute asthma before a larger, multicentre trial is proposed.